PETKUQ MEHUEY: KEARIFAN LOKAL DENGAN KESETARAAN GENDER DALAM MENJAGA HUTAN ADAT SUKU DAYAK WEHEA-KUTAI TIMUR, KALIMANTAN TIMUR - Sari Mulyani (Journal Social Politica, 2022)
abstract Forest patrols require great physical strength, so they are often viewed as men's work. But, in Nehas Lian Bing Village, the Wehea Dayak Tribe is doing equality to protect the Wehea Forest, East Kutai, East Kalimantan. Petkuq Mehuey means a group of forest rangers in the Dayak Wehea language, a tribal responsibility for the forest where they live, which happens to be included in the protected forest area of ​​Wehea. According to the local wisdom of Dayak Wehea, protecting the forest is protecting future generations as well as protecting their lives, this is a shared responsibility, men and women. This article will be descriptive with case study designs whose data will be obtained from various internet sources such as journal articles, news, and webinars related to forest protection by the Wehea community and gender equality in the value of Petkuq Mehuey. This paper will discuss Petkuq Mehuey is a form of gender equality in the Wehea Dayak community related to maintaining the sustainability of their customary forest. Petkuq Mehuey, which is a product of the local wisdom of the Dayak Wehea, is one of the efforts of indigenous peoples together with the government to protect the largest protected forest in Kalimantan. Keywords: Petkuq Muhuey, local wisdom, gender equality, forest protection.